Effects of dietary inclusion of Moringa oleifera leaf meal on growth performance of Muscovy ducklings (Cairina moschata) - Assem M. Safwat; Luis Sarmiento-Franco; Enass Abd El-khalek; Bahaa M. Abou-Shehema; Osama A. Hassan; Asmaa Sh. Elnaggar (Animal Bioscience, 2024)
Objective The current experiment was performed to investigate the influence of different dietary levels of Moringa oleifera leaf meal (MOLM) on productive performance, nutrient digestibility, blood parameters, immune response, caecal microbiota, and carcass characteristics of Muscovy ducks (Cairina moschata) during 7 to 63 d of age. Methods A total of 240 unsexed 7-d-old ducklings were distributed into five (treatment) groups; each one contained six replicates with eight ducklings each. Birds of the first group were fed basal diet without MOLM and served as control, while the other four groups were fed basal diet with 0.25%, 0.50%, 1.0%, and 2.0% MOLM inclusion level, respectively. Results The obtained results revealed that including MOLM in the diets significantly improved body weight, body weight gain, feed conversion ratio and economic efficiency compared with the control group. Among the different MOLM inclusion treatments, increasing MOLM inclusion level decreased (p<0.05) such previous parameters. Decreasing MOLM inclusion levels in duckling diets increased (p>0.05) the digestibility of organic matter, crude protein, ether extract, and nitrogen free extract, however all MOLM treatments were significantly higher than the control group. Results also revealed that feeding ducks lower MOLM inclusion levels (0.25% or 0.50%) improved blood parameters (p<0.05) compared with the higher inclusion levels (1.0% or 2.0% MOLM) and the control group. Ducks fed different MOLM levels had significantly higher phagocyte index and activity, immunoglobulin G (IgG), IgM, total antioxidant capacity, glutathione peroxidase activity, and superoxide dismutase activity compared with control group. Conclusion Despite the beneficial effects of all MOLM treatments on growth performance, nutrient digestibility, physiological status, and immune response of duckling, the increasing MOLM inclusion level in the diet had deleterious effects on such studied traits, consequently 0.25% was the best MOLM inclusion level in duckling diets.